The Limits of Indonesia’s Diplomatic Protection Obligations for Citizens Involved in Transnational Crimes in Cambodia: A Normative Analysis - Hasibuan, Guntur Hudry; Lubis, Mhd Teguh Syuhada (Al-Risalah, 2026)
This study examines the limits of Indonesia's obligation to provide diplomatic protection to Indonesian citizens (WNI) involved in transnational criminal cases in Cambodia. Using a normative legal approach with a conceptual perspective, this research analyzes the ILC Draft Articles on Diplomatic Protection (2006), the Vienna Convention on Consular Relations (1963), the UN Convention Against Transnational Organized Crime (Palermo Convention 2000), and Indonesia's national legal framework, including Law No. 37 of 1999 on Foreign Relations and Law No. 21 of 2007 on the Eradication of Human Trafficking. The findings indicate that Indonesia's protection obligations operate within three distinct levels: absolute consular obligations applicable to all detained nationals regardless of legal status; conditional protection in situations involving imminent danger; and discretionary diplomatic protection, which depends on state policy considerations and may be limited by the clean hands doctrine and Indonesia's obligations under the Palermo Convention when nationals are active perpetrators of transnational crimes. Normative gaps in the domestic implementation of the Palermo Protocol further complicate the categorization of Indonesian citizens as victims or perpetrators. The novelty of this research lies in proposing a three-tier analytical framework of state protection obligations absolute, conditional, and discretionary which clarifies the legal boundaries of diplomatic protection in cases where nationals are simultaneously involved in transnational criminal networks. These findings highlight the need for regulatory harmonization and clearer institutional coordination to ensure a coherent and accountable state response in protecting Indonesian citizens abroad.